Language, conflict and violence: Reflections on an Andean discourse - Godenzzi, Juan Carlos (1989)
Language is not only an activity placed at the service of knowledge and communication; it is also an instrument of power that acts within a society and in interpersonal relationships. Thus, speaking means, at the same time, objectifying the referential world, saying something to another and establishing bonds of either cohesion or social discrimination. As far as Peru is concerned, our geographical and social reality is "learned" under the signs of particular languages: Spanish, Quechua, Aymara and numerous other languages ​​existing in our territory.